2020
DOI: 10.1155/2020/8873865
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm ofl1-Norm andl0-Norm Regularization Algorithm for CT Image Reconstruction from Limited Projection

Abstract: The l1-norm regularization has attracted attention for image reconstruction in computed tomography. The l0-norm of the gradients of an image provides a measure of the sparsity of gradients of the image. In this paper, we present a new combined l1-norm and l0-norm regularization model for image reconstruction from limited projection data in computed tomography. We also propose an algorithm in the algebraic framework to solve the optimization effectively using the nonmonotone alternating direction algorithm with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the GA calculation, in order to make the algorithm retain the individual's good genes, the adaptive GA can be used to adjust the traditional GA adaptive degree problem. Let the crossover operator be P c , if they need to be adjusted automatically with the fitness, there is formula (5):…”
Section: Ct Image Segmentation Methods Based On Image Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the GA calculation, in order to make the algorithm retain the individual's good genes, the adaptive GA can be used to adjust the traditional GA adaptive degree problem. Let the crossover operator be P c , if they need to be adjusted automatically with the fitness, there is formula (5):…”
Section: Ct Image Segmentation Methods Based On Image Segmentationmentioning
confidence: 99%
“…Li et al has found that norm regularization has attracted attention in computerized CT scan image reconstruction. CT image gradients have provided a measure of image gradient sparsity for reconstructing images from finite projection data in CT and have effectively addressed optimization problems [ 5 ]. Scholars have seen that CT images are not only used in the medical field, but also used in various fields to a certain extent, which also shows that CT images have made great progress.…”
Section: Related Workmentioning
confidence: 99%
“…If Np, the quantitative parameters V i, i=1,Np , are present in the experimental design, the norm L p is defined by Relation (5) [63,81,82]:…”
Section: P Methodsmentioning
confidence: 99%
“…Li, X. used the transfer learning method to extract CT image features, recognize epidemic, modify the typical inception network, and use the pre training weight to fine tune the m-inception model. The experimental results show that the deep learning method is very valuable for extracting radiation image features 9 . Li, Z. based on the v-net model, using the bottleneck structure, obtained a lightweight 3D convolutional neural network VB net model, which automatically and quantitatively analyzed the volume and density of the infected area in the CT image of epidemic 10 .…”
Section: Related Workmentioning
confidence: 99%